The therapist’s personal therapy: What influence does it have on their clinical practice? - Bento, Frederico; Sousa, Daniel (European Journal for Qualitative Research in Psychotherapy, 2022)
Many studies of therapists’ experience of personal therapy and its influence on clinical practice are relatively old and focus on a particular population of therapists, namely psychoanalysts. This study explores the impact of therapists' therapy on their clinical practice across two different modalities. Semi-structured qualitative interviews were carried out with 19 therapists, all of whom had had at least one experience of personal therapy. Analysis was carried out using the descriptive phenomenological method developed by Giorgi & Sousa (2010). Eight essential themes emerged: Integrating a role model; Personal therapy: necessary work when becoming a therapist; Discovering personal and professional identity; Feeling free to be who you are; Self-awareness as a good resource; The therapeutic relationship: Presence, trust, safety, and acceptance; The importance of being a truly human person; and Becoming better therapists –more passionate, more mature, more efficient, more capable and more self-critical. While many of these themes are discussed in the existing literature, the final one (Becoming better therapists) represents a significant addition to the literature. The article concludes with some suggestions for future research.